Parallel fictitious domain method for a non-linear elliptic neumann boundary value problem - Rossi, Tuomo; Toivanen, Jari (Numerical linear algebra with applications, 1999)
Parallelization of the algebraic fictitious domain method is considered for solving Neumann boundary value problems with variable coefficients. The resulting method is applied to the parallel solution of the subsonic full potential flow problem which is linearized by the Newton method. Good scalability of the method is demonstrated on a Cray T3E distributed memory parallel computer using MPI in communication. Copyright © 1999 John Wiley & Sons, Ltd.